How to design a state education aid formula that is equitable, adequate, and politically feasible: The case of Connecticut - Bo Zhao (Federal Reserve Bank of Boston, 2021)
After being sued for inequity and inadequacy in school funding, many states have reformed their education aid policies. Using Connecticut as an example, this paper shows how to design a state education aid formula that can effectively address funding inequity and inadequacy while taking political feasibility into account. It first develops a measure of the gap between education cost and revenue capacity, both of which are estimated using school district characteristics that are outside the direct control of local officials at any given point in time. It then uses each district's cost-capacity gap to evaluate the state's existing education aid distribution. This paper shows that while larger-gap districts, on average, receive greater amounts of state aid per pupil under Connecticut's existing distributions, significant inequity and inadequacy remain. This paper proposes, as a potential solution, a gap-based formula that allocates state aid to close the cost-capacity gaps. The formula includes tools such as minimum and maximum levels of aid to increase its political appeal. The research method and the formula design that this paper presents are sufficiently general and flexible to be adapted easily and applied to other states.
Keywords: H75; I21; I22; I28; 330; education cost; revenue capacity; state education aid; aid formula